2008
DOI: 10.1134/s1068162008010160
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxylated steroid compounds from the Far Eastern starfish Distolasterias nipon

Abstract: Two new steroid glycosides: distolasteroside D6, (24S)-24-O-(beta-D-xylopyranosyl)-5alpha-cholestane-3beta,6alpha,8,15beta,16beta,24-hexaol, and distolasteroside D7. (22E,24R)-24-O-(beta-D-xylopyranosyl)-5alpha-cholest-22-ene-3beta,6alpha,8,15beta,24-pentaol were isolated along with the previously known distolasterosides D1, D2, and D3, echinasteroside C, and (25S)-5alpha-cholestane-3beta,4beta,6alpha,7alpha,8,15alpha,16beta,26-octaol from the Far Eastern starfish Distolasterias nipon. The structures of new co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
2
14
0
1
Order By: Relevance
“…Simultaneously, we isolated this com pound in a repeated study of the Far Eastern starfish Distolasterias nipon. 8 The NMR and mass spectra of compounds 4 and 5 were found to be almost identical to those reported for distolasterosides D 1 and D 2 , respectively, which were found previously in the starfish Distolasterias nipon. 9,10 Similarly, glycoside 6 was identified as pycnopodioside A detected previously in the starfish Pycnopodia helianthoides.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Simultaneously, we isolated this com pound in a repeated study of the Far Eastern starfish Distolasterias nipon. 8 The NMR and mass spectra of compounds 4 and 5 were found to be almost identical to those reported for distolasterosides D 1 and D 2 , respectively, which were found previously in the starfish Distolasterias nipon. 9,10 Similarly, glycoside 6 was identified as pycnopodioside A detected previously in the starfish Pycnopodia helianthoides.…”
Section: Resultssupporting
confidence: 50%
“…In continu ation of our studies of physiologically active steroidal metabolites from Far Eastern starfishes, 3 we studied the steroid composition of the starfish Lethasterias fusca (order Forcipulatida, family Asteriidae) collected at the experimental Marine station of the Pacific Institute of Bioorganic Chemistry (Possiet Bay, Japanese Sea). As a result, nine steroidal compounds (1)(2)(3)(4)(5)(6)(7)(8)(9) were isolated, in particular, three new steroidal glycosides, fuscasides A (1) R = OSO 3 Na (1), OH (2) (2) and desulfated minutoside A (3), three known glycosides, viz., distolasterosides D 1 (4) and D 2 (5) and pycnopodioside A (6), two known polyhydroxysteroids, viz., 5α cholestan 3β,6α,8,15β,16β,26 hexol (7) and 5α cholestan 3β,4β,6α,7α,8,15β,16β,26 octol (8), and known native aglycon of the asterosaponin series, viz., sodium 24,25 dihydromarthasterone 3 sulfate (9).…”
mentioning
confidence: 99%
“…Neuritogenic activity of steroid glycosides from the Okinawan blue starfish Linckia laevigata was revealed for the first time by Qi, Han and co-authors [4,9,10] on pheochromocytoma PC12 cells. In our previous work, we demonstrated that polar steroids (polyhydroxysteroids and related glycosides) from various species of starfish could induce neurite outgrowth in mouse neuroblastoma C-1300 cell culture [11,12,13]. The present research is devoted to more detailed study of neurotrophic activities of six starfish steroid compounds: asterosaponin Р 1 , (25 S )-5α-cholestane-3β,4β,6α,7α,8,15α,16β,26-octaol, and (25 S )-5α-cholestane-3β,6α,7α,8,15α,16β,26-heptaol, designated as PP1, PP2, and PP3 ( 1 – 3 ), from Patiria (= Asterina ) pectinifera [14], and distolasterosides D 1 –D 3 , designated as D1, D2, and D3 ( 4 – 6 ), from Distolasterias nipon [13] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we demonstrated that polar steroids (polyhydroxysteroids and related glycosides) from various species of starfish could induce neurite outgrowth in mouse neuroblastoma C-1300 cell culture [11,12,13]. The present research is devoted to more detailed study of neurotrophic activities of six starfish steroid compounds: asterosaponin Р 1 , (25 S )-5α-cholestane-3β,4β,6α,7α,8,15α,16β,26-octaol, and (25 S )-5α-cholestane-3β,6α,7α,8,15α,16β,26-heptaol, designated as PP1, PP2, and PP3 ( 1 – 3 ), from Patiria (= Asterina ) pectinifera [14], and distolasterosides D 1 –D 3 , designated as D1, D2, and D3 ( 4 – 6 ), from Distolasterias nipon [13] (Figure 1). Besides the investigation of neuritogenic activity of starfish steroids 1 – 6 at low concentrations, we analyzed their neuroprotective ability during oxygen-glucose deprivation using the mouse neuroblastoma C-1300 and organotypic rat hippocampal slice cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation